Analisis Implementasi Pembelajaran Kurikulum Merdeka di Sekolah Dasar Negeri - ramdani, Putri; Kusmaharti, Dian; Yustitia, Via (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is motivated by the low level of numeracy literacy skills of Indonesian students who get below average scores. The purpose of this study is to find out about the numeracy literacy skills of grade III students in the material of arithmetic operations of whole numbers. This study uses a descriptive method with a qualitative approach. This study was conducted on 10 grade III students of Al-Ikhlash Elementary School, Surabaya. The data collection technique was a test instrument in the form of literacy-based story questions given to 10 research subjects to determine students' numeracy literacy skills, interviews were conducted with students and with grade III elementary school homeroom teachers as supporting data on students' numeracy literacy skills. Based on the results of the study conducted on 10 students, the following results were obtained: 5 out of 10 students have a low level of numeracy literacy skills with a score below 65. 4 out of 10 students have a moderate level of numeracy literacy skills with a score below 85, and 1 out of 10 students has a high level of numeracy literacy skills because they get a score above 85